Dihydroorotate dehydrogenase inhibitor olorofim exhibits promising activity against all clinically relevant species within Aspergillus section Terrei. (23rd August 2018) - Lackner, Michaela; Birch, Mike; Naschberger, Verena; Grässle, Denise; Beckmann, Nicola; Warn, Peter; Gould, Julie; Law, Derek; Lass-Flörl, Cornelia; Binder, Ulrike
Abstract: Objectives: In vitro and in vivo activity of the dihydroorotate dehydrogenase inhibitor olorofim (formerly F901318) (F2G Limited, UK) against clinically relevant species of the Aspergillus section Terrei was evaluated. Methods: A total of 92 clinical Aspergillus section Terrei isolates [42 Aspergillus terreus sensu stricto and 50 cryptic species: Aspergillus alabamensis ( n  = 8), Aspergillus citrinoterreus ( n  = 27), Aspergillus floccosus ( n  = 1), Aspergillus hortai ( n  = 13) and Aspergillus neoafricanus ( n  = 1)] were evaluated. MICs were determined using the CLSI M38-A2 method. MICs of olorofim were compared with those of posaconazole, voriconazole, itraconazole and amphotericin B. The in vivo efficacy of olorofim was determined in an immunosuppressed murine model of disseminated aspergillosis. Results: Olorofim was highly active against all tested Aspergillus section Terrei isolates, exhibiting an MIC range of 0.002–0.063 mg/L. Slightly higher MICs were observed for A. terreus cryptic species. Olorofim MICs were lower than those observed for the azoles. Selected strains with elevated MICs of azoles were highly susceptible to olorofim. Olorofim administered by oral and intravenous routes produced survival rates of 90%–100% in A. terreus -infected mice. Conclusions: Olorofim showed potent and consistent in vitro activity against all A. terreus strains tested, including those with elevated MICs of other antifungal substances. Overall, growth inhibition by olorofim was superior to that of azoles. In vivo data showed that olorofim was highly efficacious in prolonging survival of mice with disseminated aspergillosis due to A. terreus sensu stricto.